Dicke superradiance on Landau levels - Fomin, P.I.; Fomina, A.P. (Вопросы атомной науки и техники, 2001)
It is shown that in the inverted system of nonrelativistic electrons in rarefied magnetized plasma, when electron density on high Landau levels exceed some critical value defined by its transversal energy, magnetic field and temperature, the nonequilibrium phase transition occures with domain ordering of mutual orientations of interacting rotated dipoles. The intensity of cyclotron radiation of each domain in ordered phase becomes proportional to square of electron number in it.